2021
DOI: 10.1088/1755-1315/756/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the adoption of innovation in beef cattle farming: A study in Peninsular Malaysia

Abstract: Beef cattle plays a role as a protein source to the population of a country. However, the current demand for beef is greater than its supply making it a hot issue in food security. Moreover, the price of local beef per kilogram is higher than imported beef. The use of innovations such as artificial insemination, biosecurity and integration techniques is yet to be applied by beef cattle farmers although empirically proven to improve beef production. This situation has become more critical among beef producers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They are the most wealthy farmers with the highest education levels. As observed by Lestari et al (2019) and Abdullah et al (2021), large-scale cattle farmers don't seem to perceive biosecurity or innovation incentives as a real advantage. They can sell their cattle at any time, giving them a secure business -as confirmed through communication with Universidad Nacional de Costa Rica and local cattle farmers.…”
Section: Farmer Preferences Regarding Vanilla Cultivationmentioning
confidence: 95%
“…They are the most wealthy farmers with the highest education levels. As observed by Lestari et al (2019) and Abdullah et al (2021), large-scale cattle farmers don't seem to perceive biosecurity or innovation incentives as a real advantage. They can sell their cattle at any time, giving them a secure business -as confirmed through communication with Universidad Nacional de Costa Rica and local cattle farmers.…”
Section: Farmer Preferences Regarding Vanilla Cultivationmentioning
confidence: 95%
“…The transformation of agricultural waste, including cattle waste, into organic fertiliser can generate additional income besides improving the farmers' livelihood. Abdullah et al (2021) also agreed that farmers could potentially have a better social status by producing compost. Besides, a study done among farmers on Caribbean Island by Paul et a.…”
Section: Compostsmentioning
confidence: 99%
“…However, the decision to adopt any farming-related technology is complicated [ 8 ]. A variety of factors, including socio-demographic features, farm characteristics, economic conditions, and institutional factors, may influence decision making [ [9] , [10] , [11] , [12] ]. As a result, identifying the factors' influencing adoption is critical for the livestock sector's development.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed that communication between farmers and technicians is essential for the adoption of livestock management practices in Brazil [ 9 , 10 ]. Adoption of ILMP is also influenced by education, cattle number, and information source [ 11 , 12 ]. A few studies conducted in Africa found that off-farm income, herd size, and education played important roles in adoption decision [ [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%